Managing Electricity Costs in Industrial Mining and Cryptocurrency Data Centers - Dzyuba, Anatolyy; Solovyeva, Irina; Konopelko, Dmitry (International Journal of Energy Economics and Policy, 2023)
2022 has seen a significant decline in global cryptocurrency ratings, especially bitcoin. As it is known, one of the key components of the cryptocurrency’s cost is the amount of electrical energy spent by the computing equipment of the mining data centers. In the context of declining bitcoin rates, the management of the data centers’ energy costs becomes critical for maintaining the profitability and investment return of the mining projects. Russia is among the top-3 leading producers of cryptocurrencies, providing 11% of the global primary bitcoin transactions. In this regard, the management of the data centers’ costs related to the purchase of electricity in the Russian wholesale and retail electricity (capacity) markets presents a high scientific and practical importance. This article analyzes the pricing mechanisms for the purchase of electricity in Russia’s wholesale and retail electricity (capacity) markets on an industrial scale given the specifics of the hourly demand-based pricing. This paper suggests a new metrics system, including a capacity demand management coefficient and a transmission cost management coefficient, which allow setting specific price parameters for the different components of the electricity price based on demand analytics. Simulation of different parameters of the energy cost management in mining data centers demonstrated that the ultimate electricity price can, on average, be reduced by 70% of the initial level across all regions of the Siberian Federal District of Russia. The suggested energy cost management model takes into account both internal and external factors of industrial data centers as well as monitoring of their operations along with the price factors of the wholesale and retail electricity markets. This material may be useful to specialists in the field of management of mining data centers who are involved in the operation and/or design of such facilities across various regions of Russia.